1992
DOI: 10.1111/j.1471-0528.1992.tb13733.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign ovarian cysts in England and Wales and in the United States

Abstract: Objective To compare the rates of hospital admission for management of ovarian cysts in England and Wales and the United States between 1972 and 1974 and 1984 and 1986; and to determine whether these rates are related to rates of early diagnosis of ovarian cancer. Design Analysis of published and unpublished hospital discharge data based on national samples, the Hospital In‐patient Enquiry (HIPE), a 10% hospital discharge sample for England and Wales, and the National Hospital Discharge Survey (NHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…10,66 -68 Whereas borderline epithelial cancer likely represents a precursor to type I epithelial carcinoma, such studies have not convincingly identified that benign epithelial ovarian cysts increase risk for ovarian malignancy. 9,10,66 -68 Further lending support to this theory are cohort and large prospective observational studies that indicate the removal of persistent simple ovarian cysts is not associated with a decrease in the proportion of expected deaths from ovarian cancer relative to other cancers, 69 and that monitoring of patients with unilocular ovarian cysts smaller than 10 cm without intervention is not associated with evidence of malignant transformation over the course of prolonged observation. [61][62][63][64][65] Thus, the present literature indicates that it may not always be necessary to surgically remove asymptomatic unilocular ovarian cysts thought to represent benign entities.…”
Section: Low-risk Adnexal Mass (No Surgical Intervention)mentioning
confidence: 84%
“…10,66 -68 Whereas borderline epithelial cancer likely represents a precursor to type I epithelial carcinoma, such studies have not convincingly identified that benign epithelial ovarian cysts increase risk for ovarian malignancy. 9,10,66 -68 Further lending support to this theory are cohort and large prospective observational studies that indicate the removal of persistent simple ovarian cysts is not associated with a decrease in the proportion of expected deaths from ovarian cancer relative to other cancers, 69 and that monitoring of patients with unilocular ovarian cysts smaller than 10 cm without intervention is not associated with evidence of malignant transformation over the course of prolonged observation. [61][62][63][64][65] Thus, the present literature indicates that it may not always be necessary to surgically remove asymptomatic unilocular ovarian cysts thought to represent benign entities.…”
Section: Low-risk Adnexal Mass (No Surgical Intervention)mentioning
confidence: 84%
“…This sample size (approximating the number of patients who enter such a pathway each year in the U.S.) was determined based on the number of annual ovarian cancer diagnoses in the U.S. plus an estimated rate of approximately 70% negative findings at the time of surgery for a suspected ovarian cancer [2,17]. The simulation was used to quantify the distribution of outcomes to identify the optimal pathway to diagnosis by time and number of health care events.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lack of screening or early detection strategies, it is estimated that 60,000 additional women each year are referred to gynecologic oncology for suspected ovarian cancer, representing further surgical and diagnostic procedures [2]. For those later diagnosed with ovarian cancer, the majority will have advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…One study, undertaken in the United States, estimated this as 500 admissions per 100,000 women. [2][3][4] Most clinicians who are faced with an ovarian tumor would recommend surgery or expectant management, depending on the clinical complaints and the presumed nature of the lesion. 5 In the case of suspected malignancy, surgery is mandatory, whereas tumors presumed to be benign can be managed by either a minimally invasive surgery 6 or expectant management if the patient is asymptomatic.…”
Section: Introductionmentioning
confidence: 99%